2007
DOI: 10.1007/s10495-007-0719-7
|View full text |Cite
|
Sign up to set email alerts
|

IP3 receptors in cell survival and apoptosis: Ca2+ release and beyond

Abstract: Inositol 1,4,5-trisphosphate receptors (IP 3 Rs) serve to discharge Ca 2+ from ER stores in response to agonist stimulation. The present review summarizes the role of these receptors in models of Ca 2+ -dependent apoptosis. In particular we focus on the regulation of IP 3 Rs by caspase-3 cleavage, cytochrome c, anti-apoptotic proteins and Akt kinase. We also address the evidence that some of the effects of IP 3 Rs in apoptosis may be independent of their ion-channel function. The role of IP 3 Rs in delivering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
123
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(126 citation statements)
references
References 171 publications
(219 reference statements)
3
123
0
Order By: Relevance
“…This idea is supported by observations that modulation of IP 3 R activity (by antisense knockdown, genetic deletion, or using a cell-permeable inhibitory peptide that interferes with the IP 3 R-cytochrome c interaction) rendered cells less sensitive to apoptosis triggered by both intrinsic and extrinsic pathways (Joseph and Hajnoczky, 2007). Moreover, Bcl-2 and Bcl-X L , two major antiapoptotic proteins, interact with the IP 3 R and alter its activity, though in opposite ways: Bcl-2 decreases the IP 3 R opening probability, whereas Bcl-X L increases it (Oakes et al, 2003;Chen et al, 2004;White et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
“…This idea is supported by observations that modulation of IP 3 R activity (by antisense knockdown, genetic deletion, or using a cell-permeable inhibitory peptide that interferes with the IP 3 R-cytochrome c interaction) rendered cells less sensitive to apoptosis triggered by both intrinsic and extrinsic pathways (Joseph and Hajnoczky, 2007). Moreover, Bcl-2 and Bcl-X L , two major antiapoptotic proteins, interact with the IP 3 R and alter its activity, though in opposite ways: Bcl-2 decreases the IP 3 R opening probability, whereas Bcl-X L increases it (Oakes et al, 2003;Chen et al, 2004;White et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, numerous reports have suggested that altered IP 3 R activity is involved in apoptosis in a variety of cell types (reviewed in Ref. 16). For example, initial reports showed that IP 3 Rs are required to promote apoptosis.…”
mentioning
confidence: 99%
“…Despite these reports questions remain. For example, what is the fate of the expected N-terminal fragment (16)? It is also not clear whether all of the subunits within individual tetrameric channels are cleaved during caspase proteolysis of IP 3 R1.…”
mentioning
confidence: 99%
“…IP3Rs are ligand-gated channels that serve to discharge Ca 2 þ from ER stores in response to agonist stimulation. 40,54 After IP3-mediated release of Ca 2 þ from the ER through the IP3 receptor, high-Ca 2 þ microdomains (estimated to be in the range of 50-100 mM) are generated at the tight ERmitochondrial junctions, activating the low-affinity mitochondrial Ca 2 þ uniporter and resulting in mitochondrial Ca 2 þ uptake 32 ( Figure 4).…”
Section: Ip3rs As Target Of Cell Deathmentioning
confidence: 99%